Mosque interior design and accessories for the disabled from an Islamic perspective - Jasmani, Ismail (IIUM Press, 2011)
Examines the issues that disabled people face in using the mosque to fulfil their responsibilities towards God and offers practical solutions from an Islamic perspective. Briefly explores the different functions of the mosque as community centre, learning centre, welfare centre, seat of government, prison, hospital and a place for legitimate recreational activities which is stated in the holy Quran and hadiths. Further to that the discussion on the relationship and facility between the mosque, Muslim community and disabled people, and states that the participation of people with disabilities is beneficial to the Muslim community and Mosque. The challenges involved in solving the issues to ensure the involvement of Muslim handicapped society with the larger Muslim Community.